A Comparative Analysis of Primary and Bailout ADR in CTO-PCI - Lirui Yang; Tao Zhang; Gang Wang; Leisheng Ru; Lin Zhao (Journal of Interventional Cardiology)
Conclusions: Both primary and bailout ADR are safe strategies for CTO-PCI. Primary ADR significantly improves the success rate of PCI for CTO compared to bailout ADR, with shorter operation time, lower radiation dose, and reduced contrast volume.